Development and Evaluation of Google Course-kit in Teaching Selected Basic Technology Concept in Ilorin Metropolis - Daramola, Florence Olutunu (ASEAN Journal of Educational Research and Technology, 2022)
This study is based on the development and evaluation of the Google Course-kit in teaching selected basic technology concepts in the Ilorin metropolis. The study adopted a design and development model type. The population consists of educational technology experts, computer science experts, and basic technology teachers, which were randomly selected to participate. The instrument for data collection was an adapted questionnaire. Descriptive and Inferential statistics were used to answer the research question and test the stated hypotheses with the aid of Statistical Product and Service Solution (SPSS) version 20.0 at a 0.05 level of significance. The findings indicated that postgraduate students had a positive perception of the utilization and ease of use of mobile technologies for learning. No significant difference exists in the postgraduate students’ perception of the utilization of mobile technologies for learning based on gender and the field of study. The study concluded that the teaching aids or materials such as Google kits work as a powerful tool in and outside the four walls of the classroom and can be used to enhance the teaching of basic technology in Nigeria, more particularly, Ilorin metropolis. Google kit is appreciated by the teachers and they are ready to use it in the classroom to provide the opportunity for learners to visualize materials that are not readily available in the school and to show the actual meaning of the lesson content.